Isolation of a seed coagulant Moringa oleifera lectin - Santos, Andréa F. S. (2009)
In this work hemagglutinating activity (HA) was investigated in distinct Moringa oleifera tissue extracts. A new lectin from seeds (cMoL) was purified and characterized; hemagglutinating and coagulating activities were evaluated. HA was detected in 0.15 M NaCl extracts from flowers and rachis inflorescence (5%, w/v), seeds, leaves, fundamental tissue of stem and steam bark (10%, w/v). cMoL isolated after saline extraction and guar gel column chromatography was active at pH range 4.0–9.0 agglutinating erythrocytes from rabbit and human blood types. Extracts of tissues and cMoL activities were carbohydrate inhibited; azocasein and asialofetuin abolished cMoL HA. The lectin was thermostable at 100 °C during 7 h. Polyacrylamide gel electrophoresis under reduced conditions revealed a main polypeptide band of 26.5 kDa; native basic cMoL was detected as a unique band. Seed lectin preparations and cMoL showed coagulant activity, similar to aluminium sulphate, the coagulant most widely used in water treatment.